1999
DOI: 10.1080/03079459994650
|View full text |Cite
|
Sign up to set email alerts
|

Detection of exogenous and endogenous avian leukosis virus in commercial chicken eggs using reverse transcription and polymerase chain reaction assay

Abstract: Avian leukosis retroviruses (ALV) cause lymphomas and other cancers in chickens.Previous studies have used enzyme-linked immunosorbent assays (ELISA) and indirect immuno¯uorescence assays (IFA) to detect ALV p27 group-speci® c antigens (GSA) in commercial chicken eggs. In the poultry industry eradication programme against exogenous ALV, ELISA assays are used to identify chickens infected with the virus. The inability of ELISA and IFA assays to discriminate between ALV GSA of endogenous or exogenous origin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…It is worthwhile to note that exceedingly high risk of death from zoonotic bacterial diseases and helminthiasis (up to 100-fold) is being observed in this poultry cohort (manuscript in preparation), thus reenforcing the suggestion of the possible role of transmissible agents in the occurrence of the excess of some of these cancers. Also, it is well established that some of these viruses are present in eggs destined for human consumption as reviewed by us [24] and as reported by us from a survey of eggs sold in supermarkets in the New Orleans metropolitan area [25,26]. Furthermore as mentioned above, we and others have shown that members of the general population have antibodies in their blood against ALSV and REV [27][28][29].…”
Section: Smrmentioning
confidence: 69%
“…It is worthwhile to note that exceedingly high risk of death from zoonotic bacterial diseases and helminthiasis (up to 100-fold) is being observed in this poultry cohort (manuscript in preparation), thus reenforcing the suggestion of the possible role of transmissible agents in the occurrence of the excess of some of these cancers. Also, it is well established that some of these viruses are present in eggs destined for human consumption as reviewed by us [24] and as reported by us from a survey of eggs sold in supermarkets in the New Orleans metropolitan area [25,26]. Furthermore as mentioned above, we and others have shown that members of the general population have antibodies in their blood against ALSV and REV [27][28][29].…”
Section: Smrmentioning
confidence: 69%
“…Another set was PA1 and PA2 which is nondegenerative primer. This set is specific for subgroup A (Pham et al 1999b). …”
Section: Oligonucleotide Primersmentioning
confidence: 98%
“…These viruses are responsible for serious economic losses in the poultry industry worldwide due to reduced growth rate, decreased quantity and quality of egg production, and increased sporadic tumor-induced mortality (Kim and Brown. 2004;Pham et al 1999b). In Iran, veterinary clinicians reported different types of tumor in different organs of chicken and much sporadic mortality in poultry farms (Mohammadi et al 2008; Movassaghi and Mayahi.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The RT-PCR reaction tubes also contained oligonucleotides to amplify 28S rRNA cDNA as an internal control and for standardization purposes. Pham et al (1999) used a RT-PCR to investigate the incidence of avian leukosis virus (ALV) in the eggs of ALV-exposed commercial chickens, and also in eggs randomly chosen from retail stores. To reduce the number of false positives arising from the presence of viral DNA from the cock or hen parents, RNA was extracted from the albumen of unfertilized eggs.…”
Section: Figure 4 Simultaneous Pcr and Pathotyping Of Ndv (Aldous Etmentioning
confidence: 99%